Mentoring for the professions : orienting toward the future - Howley, Aimee; Trube, Mary Barbara (Perspectives in mentoring., 2015)
This edited volume brings together conceptual and empirical work from various professional fields to inform a perspective on mentoring that goes beyond what is needed for today and orients toward what is needed for the future in order to promote healthy and productive organizations. This perspective is important because the pace of change in organizations is rapid--and increasingly so. Under conditions of rapid and on-going change, employees, students, and colleagues all are learners; and the learning needs of these adults demand meaningful and focused strategies for professional development. A major strategy with demonstrated value for fostering learning among adults is mentoring, which contributes both relational and structural support for such learning. This support helps organizations build communities of practice in which colleagues alternate the role of mentor and mentee by sharing different types of expertise and different perspectives on organizational challenges.Chapters within the book focus on theoretical perspectives on mentoring, the connection between change and mentoring, the character of the leadership that mentoring entails, the developmental processes that mentees experience, the transformation of the mentee as a result of mentoring, the value of matching mentor and mentee styles, and the role of mentoring in organizational team building. Furthermore, some chapters explore the similarities and differences in individual versus group mentoring. And some of the contributions elaborate linkages among mentoring concepts and those used in related practices such as coaching and distributed leadership.